Twisted Charge‐Transfer Antennae for Ultra‐Bright Terbium(III) and Dysprosium(III) Bioprobes. Issue 14 (5th February 2018) - Bui, Anh Thy; Roux, Amandine; Grichine, Alexei; Duperray, Alain; Andraud, Chantal; Maury, Olivier
Abstract: The design of original twisted charge transfer antennae in which a non‐planar geometry is enforced thanks to one or two bulky ortho ‐Me substituents allows us to prepare the corresponding ultra‐bright Tb III and Dy III bioprobes. The brightness of the Tb III derivative compares well with that of the benchmark Tb‐Lumi4 complex. The first bio‐imaging experiments with a Dy III luminescent bioprobe are also reported. Abstract : Twist and bright : The design of original twisted charge‐transfer antennae in which a non‐planar geometry is enforced due to one or two bulky ortho ‐Me substituents allowed the preparation of the corresponding ultra‐bright Tb III and Dy III bioprobes. The brightness of the Tb III derivative compares well with that of the benchmark Tb‐Lumi4 complex. The first bio‐imaging experiments with a Dy III luminescent bioprobe are also reported.